Depoliticized and decontextualized equality promotion in the gender equality planning of Finnish comprehensive schools - Salla Myyry; Päivi Siivonen (Nordic Journal of Studies in Educational Policy)
This study critically examines gender equality planning (GEP), which has been obligatory in all Finnish comprehensive schools since 2015. GEP has been welcomed as a promising method of systemizing perspectives on gender in Finnish basic education. A regionally representative, discretional sample of gender equality plans (N = 140) was analysed using a critical discourse approach to examine how these plans discursively bent, stretched, fixed or shrank the meaning of gender equality along with the consequences of these approaches for equality promotion. The analysis shows that the GE plans constantly bent and stretched equality to separate it from gender and fixed it to free-floating gender equality measures, which left gendered power relations undisturbed. Consequently, equality promotion was represented as depoliticized. However, through the shrinking, the contextual construction of gendered power relations was recognized, and GEP exhibited the potential to politicize gender equality. In this paper, we argue that GEP has potential in gender equality promotion if the planning processes recognize contextual construction of gendered power relations and if equality promotion is not reduced to technical measures. Otherwise, the tool might actually impede equality rather than promoting it.